2019
DOI: 10.1186/s13023-019-1123-4
|View full text |Cite
|
Sign up to set email alerts
|

Share and protect our health data: an evidence based approach to rare disease patients’ perspectives on data sharing and data protection - quantitative survey and recommendations

Abstract: Background The needs and benefits of sharing health data to advance scientific research and improve clinical benefits have been well documented in recent years, specifically in the field of rare diseases where knowledge and expertise are limited and patient populations are geographically dispersed. Understanding what patients want and need from rare disease research and data sharing is important to ensure their participation and engagement in the process, and to ensure that these wishes and needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(161 citation statements)
references
References 29 publications
3
154
1
3
Order By: Relevance
“…Fifth, patients in this study expressed only few concerns about the for-profit/not-for-profit nature of organizations, explaining that even if pharmaceutical companies are driven by profit, their profit is made by developing products that benefit patients, thus ultimately all medical research serves the same purpose. This finding is somewhat contrary to the results from previously published quantitative studies, which indicated that research participants and rare diseases patients were more likely or comfortable to allow their data to be shared with not-for-profit stakeholders (e.g., academic researchers, health care professionals, non-profit and patient organizations) than with researchers in for-profit companies or insurance companies (31,32,35,36). Yet, most participants in our study did mention that they deplore a lack of collaboration and sharing between researchers because of commercial reasons.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Fifth, patients in this study expressed only few concerns about the for-profit/not-for-profit nature of organizations, explaining that even if pharmaceutical companies are driven by profit, their profit is made by developing products that benefit patients, thus ultimately all medical research serves the same purpose. This finding is somewhat contrary to the results from previously published quantitative studies, which indicated that research participants and rare diseases patients were more likely or comfortable to allow their data to be shared with not-for-profit stakeholders (e.g., academic researchers, health care professionals, non-profit and patient organizations) than with researchers in for-profit companies or insurance companies (31,32,35,36). Yet, most participants in our study did mention that they deplore a lack of collaboration and sharing between researchers because of commercial reasons.…”
Section: Discussioncontrasting
confidence: 96%
“…Fourth, all but two patients expressed their trust in ethics committees taking up the task of intermediary decision maker. In a previous quantitative study with 2,005 patients with rare diseases, about half of the respondents indicated that they would allow an ethics committee to decide on their behalf (35). Our finding reflects the practices as prescribed by ethical recommendations such as the Helsinki Declaration, although not echoed in all legal frameworks since the EU data protection framework does not stipulate any intermediary form of control for secondary re-use of sensitive data.…”
Section: Discussionmentioning
confidence: 49%
“…Other studies focused on health consumers' attitudes to secondary data usage in individuals: attending US Veterans Affairs (VA) facilities [40] or recently discharged from tertiary care [15], or with arthritis and other chronic conditions [36]. Others were in the setting of human immunodeficiency virus (HIV) [49], breast cancer (BC), colon cancer (CC) [35], or heterogeneous cancers [19,20], acquired immune deficiency syndrome (AIDS), or multiple sclerosis (MS), or mental health concerns [23], presenting with rare diseases [16,17], in adults or parents of children with cystic fibrosis (CF), sickle cell disease (SCD), or diabetes mellitus (DM) [35], or in adults with potentially stigmatising health conditions (DM, hypertension, chronic depression, alcoholism, HIV, BC, or lung cancer) [46].…”
Section: Study Design Location Clinical Focus and Study Populationsmentioning
confidence: 99%
“…If a personal connection with the research team is established, then it is easier for individuals to form a trusting relationship [23]. The highest levels of trust was placed in the doctor [16,26,46], the National Health Service (NHS) [26], and hospitals [16,46], while the lowest trust was in commercial organisations [26], pharmaceutical companies and insurance companies [46], or for-profit organisations [16]. An individual's trust in an organisation was a determinant of what level of control they preferred over their data [40] and their willingness to participate in research [42], with trust overcoming concerns about privacy and confidentiality [49].…”
Section: Themes Trustmentioning
confidence: 99%
“…Furthermore, there is a need for discussion on ensuring the data we generate is publicly available, whilst protecting patient confidentiality, to enable large scale collaborative efforts, a phenomenon which would be particularly helpful for diagnosing currently undiagnosed patients. Such a discussion and development of resources should involve continuous consultation with patients and their family members [16,153].…”
Section: Triglyceride Deposit Cardiomyovasculopathy Unknownmentioning
confidence: 99%